THE EFFECT OF LOCAL TAXES, LOCAL LEVIES, AND BUMD PROFITS ON INCREASING LOCAL ORIGINAL REVENUE (PAD) IN PACITAN REGENCY - Dewi, Rizqi Silviana; Ratnawati, Dyah (Yayasan Education and Social Center, 2023)
Local Original Revenue is relied upon as a source of organizing development and providing the best services for the community. The components of PAD include local taxes, local levies, the results of the management of separated local assets, and other legitimate PADs. In addition to these four (4) sources, the existence of BUMD also affects PAD, which fills the post of other legitimate PAD. The purpose of this study is to test and prove the effect of local taxes, local levies, and BUMD profits on increasing PAD in Pacitan Regency. The data used in this study are quantitative data based on the method of collecting documentation data from third parties at the Pacitan Regency Local Revenue Agency. The population of this study were 5 Budget Realization reports and 5 BUMD Financial Reports. Using saturated sampling technique, which makes the entire population as a research sample. The data analysis technique used in this research is Partial Least Square (PLS). The results showed that local taxes had no contribution to increasing local revenue , local Levies had no contribution to increasing local revenue, and BUMD profits had a contribution to improving local revenue